Respuesta :

Hi

f(x) = g(x)   if    -x²+3x-2   - ( -x+1) = 0

                      -x² +3x-2 +x-1 = 0

                      -x² +4x -3 = 0

To solve, tou have to use the general method of resolution of a quadratic fonction.  

To determine if it's has a solution in R, let's calculate  Δ

Δ = (4)² - 4 * (1) *(-3)

Δ = 16 +12

Δ= 28  

as Δ≥ 0  so  the function allow two solution within R  

so S 1 =  ( -4 +√28) / 2            S 2 =   (-4 -√28 ) /2

    S1 =   ( -4 + 2√7) /2            S2 =    (-4 - 2√7) /2

    S1 =    (2 (-2 +√7) /2            S2      2 (-2 -√7)   /2

    S1 =    -2 +√7                       S2 =      -2 -√7

So the two function  are equal   twice. one  for   x = -2 +√7  and second x = -2-√7